The Transformation of Arabic Language Instruction in Islamic Boarding Schools: An Analysis of the Amtsilati and Auzan Methods - Irma, Ade; Subhan, Subhan; Ghufron, Zaki; Kusni, Nikmatullah; Kuakul, Yuttana (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This study analyzes the implementation of the Amtsilati and Auzan methods as innovative, time-efficient solutions for accelerating Arabic language mastery in Islamic boarding schools. Employing a qualitative descriptive approach, data were gathered through observations, interviews, and documentation. The results demonstrate distinct operational pathways for both methods. The Amtsilati method at Miftahul Khair Curung Islamic Boarding School, Tangerang, mirrors its central model by utilizing the non-class-based fastabiqul khairat system, where student progression depends strictly on individual volume evaluations. Conversely, the Auzan method incorporates a majelis group framework, an ilqa (conveyance) system, and a muhafazah (memorization) system structured across three hierarchical levels (qira'at, tarjamah, and insya), paired with an active parental progress-reporting mechanism that enhances learning control. However, this study is limited by its qualitative, localized case-study design, which restricts broader statistical generalizability. Future research should employ comparative-experimental frameworks and develop standardized quantitative assessment tools to empirically measure the long-term linguistic proficiency outcomes of both methods across diverse institutional contexts.